2009
DOI: 10.1532/lh96.08015
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Phenotypic Expression of the T-Cell-Associated Antigen CD8 on B-Cell Chronic Lymphocytic Leukemia Cells

Abstract: B-cell chronic lymphocytic leukemia (B-CLL) is a heterogeneous hematologic malignancy caused by a clonally expanded B-cell population that recirculates between the blood and tissues. Described is the case of an 81-year-old female B-CLL patient with aberrant expression of a T-cell-associated antigen, CD8, on CD19+ B-CLL cells. Despite chlorambucil therapy and a subsequent salvage regimen, the patient rapidly entered progressive disease and died 9 months later. Flow cytometric immunophenotyping of the B-CLL cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Two of the five patients died 1 and 6 years later (13). Stagno et al described an 81‐year‐old patient with CD8‐positive CLL with progressive disease despite chlorambucil and subsequent salvage therapy and assumed that aberrant CD8 expression might be related to aggressive clinical courses (14). Islam et al documented a patient with B‐CLL and aberrant coexpression of CD8 who required no therapy during the first 6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the five patients died 1 and 6 years later (13). Stagno et al described an 81‐year‐old patient with CD8‐positive CLL with progressive disease despite chlorambucil and subsequent salvage therapy and assumed that aberrant CD8 expression might be related to aggressive clinical courses (14). Islam et al documented a patient with B‐CLL and aberrant coexpression of CD8 who required no therapy during the first 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that aberrant CD8 coexpression can as well occur at diagnosis of the CLL or during the course of disease (12). The prognostic impact of aberrant CD8 coexpression for CLL patients remains unclear: some authors suggested that prognosis of patients with B‐cell lymphomas was not negatively influenced by CD8‐positivity (10, 11), whereas others were uncertain with regards to the prognostic impact (13) or speculated about more aggressive clinical behavior (14).…”
mentioning
confidence: 99%
“…Some reports suggested that CD8 expression was associated with a favorable prognosis either in terms of lack of progression or good response to treatment [4][5][6][7][8][9][10][11][12]; however, other reports suggested CD8 as a marker of aggressive disease [13,14]. Our patient showed an indolent clinical course.…”
Section: Discussionmentioning
confidence: 60%
“…3C). There have been reports of aberrant expression of CD8 by B cells, but they have been in the context of chronic lymphocytic leukemia 49,50 or Non-Hodgkin lymphoma. 51 Steady increased expression of CD8 by B cells was also seen for naive macaques after infection with SIV, reaching similar levels to the ones seen for vaccinated macaques by 3 weeks postchallenge.…”
Section: Discussionmentioning
confidence: 99%